Efficient extraction of natural dye from red sandal wood (Pterocarpus Sandalinus) using ultrasound. (2nd January 2017) - Sivakumar, Venkatasubramanian; Rani, K.; Kumari, M.
Abstract : Red sandal wood (RSW) is one of the important natural materials yielding red colour for variety of applications. Extraction of natural dye attached to the wood matrix of RSW is difficult due to mass transfer resistance. The paper describes attempts to get efficient extraction of RSW at ambient conditions using ultrasound (even dispensing with organic solvents) as compared to magnetic stirring. Process parameters studied included the effect of time, temperature, ultrasound power, pulse mode and solvent ratio. Results indicate that up to 32% increase in yield of the sandal wood natural dye extract could be achieved using ultrasound. This methodology for RSW could be beneficial to enhance the yield and usage of this natural resource in an effective manner.